2021
DOI: 10.3389/fcosc.2021.736633
|View full text |Cite
|
Sign up to set email alerts
|

Higher Genetic Diversity of the Common Sea Cucumber Holothuria (Halodeima) atra in Marine Protected Areas of the Central and Southern Ryukyu Islands

Abstract: Recently, sea cucumbers (Echinodermata: Holothuroidea) have been over-exploited in many areas of the world, including in the Ryukyu Islands, southern Japan, due to increases in their economic importance. Nevertheless, management and protection of sea cucumbers are insufficient worldwide. The black sea cucumber Holothuria (Halodeima) atra Jaeger, 1833, inhabits a large range across the Indo-West Pacific Ocean and is a widely harvested species. Here we conducted population genetic analyses on H. atra using parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Among sites, Aka showed the highest number of individuals (131 individuals) and density (0.0903 ind/m 2 ) of H. atra , and this site is within Keramashoto National Park (see Fig. 1 for its location), which was reported recently to harbor the highest genetic diversity of this species ( Hamamoto et al, 2021 ). As well, Manza, which showed the second highest COI genetic diversity ( Hamamoto et al, 2021 ) and had the second highest total individual numbers following Aka, and third highest total population density among sites in the current study, is within a quasi-national park.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Among sites, Aka showed the highest number of individuals (131 individuals) and density (0.0903 ind/m 2 ) of H. atra , and this site is within Keramashoto National Park (see Fig. 1 for its location), which was reported recently to harbor the highest genetic diversity of this species ( Hamamoto et al, 2021 ). As well, Manza, which showed the second highest COI genetic diversity ( Hamamoto et al, 2021 ) and had the second highest total individual numbers following Aka, and third highest total population density among sites in the current study, is within a quasi-national park.…”
Section: Discussionmentioning
confidence: 69%
“…1 for its location), which was reported recently to harbor the highest genetic diversity of this species ( Hamamoto et al, 2021 ). As well, Manza, which showed the second highest COI genetic diversity ( Hamamoto et al, 2021 ) and had the second highest total individual numbers following Aka, and third highest total population density among sites in the current study, is within a quasi-national park. Combined, these facts may indicate this species is comparatively better conserved within parks.…”
Section: Discussionmentioning
confidence: 86%
“…While that study showed that habitat also influenced holothurian presence, the authors concluded that MPAs may help conserve high densities of economically important holothurians. Another study has demonstrated higher genetic diversity of H. atra within an MPA (Hamamoto et al, 2021). In general, no-take MPAs have not been designed specifically for holothurians (Cariglia et al, 2013), and the use of MPAs for holothurian conservation warrants further consideration (Hamel et al, 2022).…”
Section: Holothurians Fishing and Mpa Effectsmentioning
confidence: 99%
“…The ndings largely supported the presence of genetic variations within populations of H. fuscogilva. Moreover, the observation with AMOVA was also the case with species within its genera, among them, being H.scabra (Gardner & Fitch, 2012; Ravago-gotanco & Kim, 2019), H. mammata (Valente et al, 2015)d halodeima (Hamamoto et al, 2021), all showing high variation at the intra-population level. The variation in intrapopulation levels could be explained by the possibility of high gene ow among the locations that make up the populations, as was also suggested for H. polii populations sampled within their smaller geographic scales (Vergara-Chen et al, 2010).…”
Section: Phylogeneticsmentioning
confidence: 81%